Crises in civil society organisations: opportunities for transformation. Issue 5 (3rd July 2016) - Taylor, James
ABSTRACT: This viewpoint explores the possibility of successful civil society formations using a crisis of opportunity for transformation. Such crises reflect the need and creative energy for transformation emerging out of internal development processes. These are important moments for innovative change, not top-down or bottom-up, but from the inside out. The paper uses the experience of a South African organisation (Community Development Resource Association) that has been serving the organisational development needs of civil society organisations for 28 years. It draws specifically from work with one of South Africa's most successful CSOs (Treatment Action Campaign) over the past two years.